1989
DOI: 10.1038/bjc.1989.399
|View full text |Cite
|
Sign up to set email alerts
|

Semen cryopreservation in men undergoing cancer chemotherapy – a UK survey

Abstract: The price that many young men pay for the curative treatment of malignant disease is infertility. It has been appreciated for many years that anti-cancer treatment may result in azoospermia (Sutcliffe, 1987), which is frequently permanent (Da Cunha et al., 1984). The damage to the testes depends partly on the choice of drug -alkylating agents do the most harm (Roeser et al., 1978;Miller, 1971) -and partly on the duration of exposure (Waxman, 1985

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…Although there are anecdotal reports of successful pregnancies following the use of cryopreserved semen in men with Hodgkin's disease (Scammell et al, 1985;Redman et al, 1987;Milligan et al, 1989), to our knowledge, there are no published data describing the proportion of long term survivors of Hodgkin's disease in the UK who attempt assisted reproduction and achieve success. Our retrospective data show that most patients have not used their cryopreserved semen (27% utilisation 10 years from storage, Figure 3) the reasons for which are unclear.…”
Section: Discussionmentioning
confidence: 94%
“…Although there are anecdotal reports of successful pregnancies following the use of cryopreserved semen in men with Hodgkin's disease (Scammell et al, 1985;Redman et al, 1987;Milligan et al, 1989), to our knowledge, there are no published data describing the proportion of long term survivors of Hodgkin's disease in the UK who attempt assisted reproduction and achieve success. Our retrospective data show that most patients have not used their cryopreserved semen (27% utilisation 10 years from storage, Figure 3) the reasons for which are unclear.…”
Section: Discussionmentioning
confidence: 94%
“…Many men diagnosed with cancer have such poor quality ejaculates in terms of sperm count and motility that their cryopreserved semen is inadequate for pregnancy attempts by intra-uterine insemination (IUI) or in vitro fertilization (IVF). [5][6][7][8][9][10][11][12] Moreover, 20 -58% of patients have been shown to regain sperm production within several years after treatment, depending on the modality employed. 13,14 Patients undergoing treatment for testicular carcinoma may demonstrate even higher rates of fertility within 2-10 years after cancer therapy.…”
mentioning
confidence: 99%
“…15 Accordingly, the effectiveness of and need for cryopreservation of sperm from male cancer patients has been a point of recent debate. [5][6][7][8][9][10][11][12] The technology of assisted reproductive techniques (ART) in recent years has progressed at a tremendous pace. Today, cryopreservation of sperm with subsequent ART can provide most posttherapy infertile cancer patients an opportunity to father children.…”
mentioning
confidence: 99%
“…The assessment of the rate of assisted reproduction treatment using frozen spermatozoa in male cancer patients is relevant considering that some authors have raised doubts about the justification of banking spermatozoa 1, 7, 8. Although the probability of achieving a pregnancy using frozen spermatozoa is high, especially with the development of the ICSI procedure, it has been reported that only a few patients return for assisted reproductive treatments using frozen spermatozoa 1, 9–13.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to a survey of male cancer survivors, only 24% of childless men had banked sperm before undergoing treatment 6. In recent years, many have raised doubts concerning the justification and necessity of young men banking spermatozoa before chemotherapy and/or radiotherapy because of the relatively small number of children born as a result of using cryopreserved spermatozoa 1, 7, 8. In the few available series on this topic, relatively few patients returned for fertility treatment using frozen spermatozoa 1, 9–13.…”
Section: Studies On the Rate Of Assisted Reproductive Treatments Usinmentioning
confidence: 99%